Shadows of a sunbelt city : the environment, racism, and the knowledge economy in Austin - Tretter, Eliot (Athens : The University of Georgia Press, 2016)
"Austin, Texas is generally depicted as one of the great urban success stories of the past half century--a place that has grown enormously through 'creative class' strategies that emphasize diversity and environmental consciousness. Eliot Tretter's book reinterprets this familiar story by exploring the racial and environmental underpinnings of the postindustrial knowledge economy. He is particularly attentive to the role of the University of Texas (often working with federal, municipal, and private-sector partners), and the book will join a growing critical literature about how universities shape urban environments"--Provided by publisher.
Part 1. Forces of growth -- The making of a globalized Austin : the environment, racism, and the knowledge economy -- The value of knowledge : the expansion of the University of Texas, urban renewal, and the blackland -- Bringing in the state : state entrepreneurialism, the university, land development, and the high-technology sector -- Part 2. Urban transformations -- Sustaining a higher quality of life : the environment, crime, and the remaking of Austin's downtown -- Contesting sustainability : "smart growth" and the redevelopment of Austin's east side -- What is past is prologue : urban governance, comprehensive planning, and political reform -- Reflections: Outside the shadows.
Includes bibliographical references and index.
Keywords: University of Texas at Austin; University of Texas at Austin; Urban ecology (Sociology) -- Texas -- Austin; Racism -- Texas -- Austin; Knowledge economy -- Texas -- Austin; City planning -- Texas -- Austin; Universities and colleges -- Social aspects -- Texas -- Austin; Universities and colleges -- Environmental aspects -- Texas -- Austin; City planning; Ecology; Economic history; Knowledge economy; Race relations; Racism; Universities and colleges -- Environmental aspects; Universities and colleges -- Social aspects; Urban ecology (Sociology); Austin (Tex.) -- Environmental conditions; Austin (Tex.) -- Race relations; Austin (Tex.) -- Economic conditions; Texas -- Austin